Hypertensive Disorders of Pregnancy – A Life-Long Risk?! - Schausberger, C. E.; Jacobs, V. R.; Bogner, G.; Wolfrum-Ristau, P.; Fischer, T. (Geburtshilfe und Frauenheilkunde, 2013)
Background: Arterial hypertension is one of the most important causes of cardiovascular diseases, and the latter are responsible for almost half of the deaths in the industrialised nations. Hypertensive disorders of pregnancy constitute one of the most frequent causes of feto-maternal morbidity and mortality; on the other hand the occurrence of a hypertensive disorder of pregnancy represents a risk for the later development of hypertension and the cardiovascular risks resulting therefrom. The aim of this article is to demonstrate the association of hypertensive disorders of pregnancy with consecutive cardiovascular diseases. Materials and Methods: Specific selective literature research. Results: After the occurrence of a hypertensive disorder of pregnancy the relative risks for hypertension are 3.7 (2.70–5.05), for ischaemic heart disease 2.2 (1.86–2.52), for cerebral insult 1.8 (1.45–2.27) and for mortality resulting from cardiovascular causes 1.5 (1.05–2.14) and are thus significant. According to a recent study 56 % of internal specialists and 23 % of gynecologists do not know about the association of preeclampsia with ischemic heart disease, 48 % and 38 % respectively are not aware of the link with stroke and 79 % and 77 % respectively are not aware of the association with a reduced life expectancy after preeclampsia. The presence of hypertension is not known by many of the patients, merely 28–38 % receive an appropriate therapy. Conclusion: Adequate follow-up after hypertensive disorders of pregnancy and the early recognition of and therapy for hypertension represent the cornerstones in the prevention of late cardiovascular sequelae. General practitioners, specialist for internal medicine and gynaecologists have a special responsibility with regard to the reduction of later complications.
Keywords: hypertensive disorders of pregnancy; arterial hypertension; cardiovascular risks; follow-up; prevention